Tofu Processing at UD Sari Makmur, Wakobaloagung Village, Kabangka District, Muna Regency - Reza Reza; Dhian Herdhiansyah; Sakir Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2022)
This study aims to determine the process of making tofu products at UD Sari Makmur in Wakobaloagung Village, Kabangka District, Muna Regency. The data was collected using literature study, interviews, observation, and documentation methods. The comparative method analysis results still show that UD Sari Makmur is the producer of tofu, and the main staple is soybeans, where tofu is one of the staple food ingredients in Indonesia. Tofu is also a food that contains many nutrients and is relatively easy to produce. UD Sari Makmur is included in the small and medium enterprises (SMEs) category. The method of making tofu is still simple. Namely, preparation, soaking and washing, grinding, cooking, filtering, printing, cutting, and ready to be marketed. So that the role of the individual, in this case, the worker, is enormous in the tofu production process.